The impact of adaptation of technology towards business sustainability of King's Bakeshop - Chua, Wendyl Beatriz (Animo Repository, 2023)
Technology can reduce product waste, chemical use, and resource use while increasing production, efficiency, and cost savings. Additionally, it can review, analyze, and monitor progress, all of which can help lessen the negative effects on the environment and successfully achieve and maintain corporate sustainability, particularly in the bakery sector. Much like any other businesses, King’s Bakeshop Main Branch was also aiming to achieve business sustainability and thus the study assesses how the adaptation of technology can be used to achieve this. The results of the study showed that the company is open to integrating technology, however, several adjustments are still needed. The employees of King’s Bakeshop have an understanding about the current status of the company’s use of technology in the business, thus coinciding with the findings which showed that there is a relationship between the employee’s position to business sustainability. As such, this study can be helpful in enhancing the adaptation of technology towards achieving the business sustainability of King’s Bakeshop.